Integrasi Analitik Pendidikan dan Q-Methodology dalam Pengembangan Model Evaluasi Kurikulum Multidimensi - Fitriani Nurhayati; Imas Khotimah; A.H. Eviyani; Ihsan Abdurahman; Moh. Erihadiana; Qiqi Yuliati Zaqiah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
The study addresses a critical limitation of conventional evaluation models such as Tyler, CIPP, and Kirkpatrick, which tend to emphasize linear outcomes while inadequately capturing learning processes, stakeholder subjectivity, and the growing role of digital technologies in education. Using the PRISMA protocol, this review analyzes peer-reviewed Scopus-indexed articles published between 2013 and 2025. The search process yielded 250 articles, which were systematically screened and refined to eight core studies that explicitly examined technology-integrated evaluation, data analytics, or Q-Methodological approaches. Bibliometric mapping using VOSviewer and trend analysis with R Studio were employed to identify conceptual patterns, methodological tendencies, and research gaps. The findings are synthesized at a conceptual level and reveal three core insights. First, curriculum evaluation research is increasingly data-driven, with learning analytics and machine learning used to predict performance, engagement, and learning trajectories, yet these approaches remain largely reductionist when detached from contextual meaning. Second, Q-Methodology consistently emerges as a robust method for capturing structured subjectivity, enabling the identification of distinct stakeholder perspectives that are otherwise overlooked in metric-based evaluation models. Third, the reviewed studies demonstrate that neither analytics nor Q-Methodology alone can adequately support holistic evaluation; rather, their integration enables a multidimensional assessment encompassing cognitive, affective, behavioral, and social domains of learning. This study contributes theoretically to educational management by conceptualizing curriculum evaluation as an adaptive, formative, and socio-technical process rather than a static measurement activity. The proposed hybrid framework positions evaluation as a strategic tool for decision-making, organizational learning, and curriculum governance. Practically, the findings are particularly relevant for developing education systems such as Indonesia’s Kurikulum Merdeka, where contextual diversity, digital transition, and stakeholder participation demand more inclusive and responsive evaluation models. By articulating a conceptual synthesis rather than a procedural template, this article advances curriculum evaluation scholarship toward a holistic and future-oriented paradigm.